CLUSTER STRUCTURE OF ORGANIZATION OF IMMUNE STATUS IN PATIENTS WITH URGENT SURGICAL PATHOLOGY - P. V. Sarap (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The immune system of patients with urgent surgical pathology is affected by multiple damaging factors. Their action leads to the formation of separate clusters with centers at points corresponding to the optimal characteristics of the immune system. The distance from the cluster center (DC) is closely related to the patient. In order to characterize the features of indicators of the patients in the central and peripheral areas of clusters 442 patients with urgent abdominal pathology were examined. Using the number of CD3+, CD4+, CD8+, CD16+ lymphocytes allocated six clusters of immune status. We compared the patients belonging to the central and. peripheral quantiles of each cluster. The results show that the peripheral area of the clusters are characterized by high values of indicators of intoxication and severity of the condition. Indicators show most intensity of the immune system and autonomic regulation in the periphery of the clusters. Cluster membership and DC are important criteria for evaluating the severity of the patients and to optimize treatment methods.